Rivastigmine Regulates the HIF-1α/VEGF Signaling Pathway to Induce Angiogenesis and Improves the Survival of Random Flaps in Rats - Liu, Yingying; Li, Wenjie; Ma, Xinyi; He, Jibing; Lin, Yi; Lin, Dingsheng (Frontiers in Pharmacology, 2022)
Random skin flaps are frequently used to repair skin damage. However, the ischemic and hypoxic necrosis limits their wider application. Rivastigmine, a carbamate cholinesterase inhibitor (ChEI), has also been shown to reduce ischemia–reperfusion injury (IRI) and inflammation. This study was performed to examine the effect of rivastigmine on flap survival. Sixty male Sprague–Dawley rats with a modified McFarland flap were randomly divided into three groups: control group, 1 ml of solvent (10% DMSO + 90% corn oil); low-dose rivastigmine group (Riv-L), 1.0 mg/kg; and high-dose rivastigmine group (Riv-H), 2.0 mg/kg. All rats were treated once a day. On day 7, the skin flap survival area was measured. After staining with hematoxylin and eosin (H&E), the pathological changes and microvessel density (MVD) were examined. The expression of inflammatory factors IL-1β and IL-18, CD34, hypoxia-inducible factor-1α (HIF-1α), and vascular endothelial growth factor (VEGF) was examined by immunohistochemical staining. The malondialdehyde (MDA) content and superoxide dismutase (SOD) activity were examined to determine the degree of oxidative stress. Lead oxide/gelatin angiography showed neovascularization and laser Doppler blood flowmetry showed the blood filling volume. Rivastigmine significantly increased the flap survival area and improved neovascularization. CD34, VEGF, and HIF-1α expression were increased, These changes were more pronounced in the Riv-H group. Treatment with rivastigmine reduced the level of MDA, improved SOD activity, and reduced expression of IL-1β and IL-18. Our results indicate that Rivastigmine can increase angiogenesis and significantly improve flap survival.